Synthesis and crystal structure of the novel metal organic framework Zn(C3H5NO2S)2. Issue 4 (9th September 2014) - Ferrer, P.; da Silva, I.; Rubio-Zuazo, J.; Castro, G. R.
<x content-type="archive" xml:space="preserve">Abstract</x> The crystal structure of the novel metal organic framework (MOF) Zn(C3H5NO2S)2 is described. This MOF can serve as a model for active sites in metalloproteins, on diverse activities such as structural or catalytic functions. Each half of the amino acid act as a bidentate ligand to one Zn and as a monodentate ligand to another Zn, while the disulphide bond presents an important structural function, stabilizing the crystal packing. The structure has been obtained ab initio from synchrotron X-ray powder diffraction data. The compound crystallizes in the orthorhombic system (space group P212121), with a = 20.0906(7), b = 9.5842(3), c = 5.018 89(13), and V = 966.40(5) Å3, with Z = 4. The structure was determined using a direct space approach, by means of the Monte Carlo technique, followed by Rietveld refinement.